Wave-Packet Convergent Close-Coupling Approach to Ion Collisions with Atoms and Molecules - Plowman, Corey Thomas (Curtin University, 2023)
The two-centre wave-packet convergent close-coupling method has been applied to generate a comprehensive set of data for collisions between numerous ions and atoms of importance to plasma modelling for fusion energy and hadron therapy. Results for differential scattering provide a detailed characterisation of the collision process, giving insight into the underlying physics. Furthermore, extension to proton collisions with hydrogen molecules has produced the first accurate description of the energy and angular distribution of emitted electrons.